Pengaruh Variasi Gula Terhadap Karakteristik Sediaan Minuman Serbuk Instan Kombinasi Rimpang Jahe Dan Temu Putih - Desy Siska Anastasia; Sri Luliana; Rise Desnita; Isnindar Isnindar; Nur Atikah (Journal Syifa Sciences and Clinical Research, 2022)
The combination of ginger and white turmeric is the right way to make instant powder drink preparations. The content of gingerol in ginger and curcumin in white turmeric is useful as a natural diuretic (urine laxative). Instant powder drink preparations are made of 2 formulas with different variations of sweeteners, namely formula 1 with 100% granulated sugar and formula 2 with a combination of granulated sugar and brown sugar (3:1). This study was to determine the effect of variations in sugar on physical characteristics and the level of preference of panelists for the preparation of an instant powder drink containing a combination of ginger rhizome and white turmeric. Making instant powder drinks using the crystallization method Physical test data was analyzed by the Independent Sample T-Test. The test results showed that the two formulas met the powder test requirements with the pH value, setting, moisture content, flow time, and angle of repose in formula 1 each being 6.53; 9.3%; 0.26%; 15.63 grams/second; and 31.62, while formula 2 is 6.19; 5.6%; 1.04%; 11.55 grams/second; and 36.44. The hedonic test shows that there is a significant difference in preference values where formula 2, with a combination of sugar and brown sugar (3:1), is more preferred by the panelists.